The Impact of the Four-year Learning Programme to Students’ Career Aspirations: : The Case of University of Botswana Accounting and Finance Students - Dzimiri, Mashoko Tserere; Mapharing, Mogotsinyana; Ndzinge, Shabani (Advances in Social Sciences Research Journal, 2019)
The paper determines whether the students’ career aspirations have changed from the time they enrolled for a particular programme during the first year until they have encountered socialisation throughout the four-year learning period, which includes the internship programme. Descriptive research design was used in the study. The research population for the study were all final year University Botswana undergraduate business students on a four year study programme. Purposive sampling was used to select a total of 100 students from the final year Accounting and Finance students and, the two groups being equally represented in the sample. Primary data was used for the study and collected using a 5-point Likert scale questionnaire from the two groups during class time. Descriptive statistics and Independent sample t-tests were used to analyse the data. The internship programme is an eye opener to the students and help them to prepare for their careers. The students who enrolled for the accounting and finance programmes stuck to the careers choices they had made at the commencement of their four year study programmes. The university must continue with internship programmes, if possible assist finance students to secure internship places in finance related institutions both locally and regionally.